Dopamine Transporter, Age, and Motor Complications in Parkinson's Disease: A Clinical and Single‐Photon Emission Computed Tomography Study. Issue 6 (10th March 2020) - Palermo, Giovanni; Giannoni, Sara; Frosini, Daniela; Morganti, Riccardo; Volterrani, Duccio; Bonuccelli, Ubaldo; Pavese, Nicola; Ceravolo, Roberto
Abstract: Background: Previous molecular imaging studies comparing dopamine function in vivo between early‐onset PD and late‐onset PD patients have shown contradictory results, presumably attributable to the aging‐related decline in nigrostriatal function. Objectives: (1) To investigate baseline dopamine transporter availability in early‐onset PD (<55 years) and late‐onset PD (>70 years) patients, z‐scores values of putamen and caudate [ 123 I]‐ioflupane uptake were calculated using the respective age‐matched controls in order to correct for early presynaptic compensatory mechanisms and age‐related dopamine neuron loss; (2) to examine the associations of such baseline single‐photon emission computed tomography measures with the emergence of late‐disease motor complications. Methods: In this retrospective study, 105 de novo PD patients who underwent [ 123 I]‐ioflupane single‐photon emission computed tomography at time of diagnosis were divided into three tertile groups according to age at disease onset (35 early‐onset PD and 40 late‐onset PD patients). Z‐scores were compared between the two groups, and their predictive power for motor complications (during a mean follow‐up of 7 years) was evaluated using Cox proportional hazard models. Results: Despite a less‐severe motor phenotype, early‐onset PD patients exhibited more reduced [ 123 I]‐ioflupane binding in the putamen and had a higher and earlier risk for developing motor complications than those with late‐onset PD. Lower [ 123 I]‐Ioflupane uptake in the putamen and caudate increased the risk of motor complications. Conclusions: Our findings indicate that a lower dopamine transporter binding in early‐onset PD predicts the later development of motor complications, but it is not related to severity of motor symptoms, suggesting age‐related differences in striatal compensatory mechanisms in PD. © 2020 International Parkinson and Movement Disorder Society